1999
DOI: 10.1002/(sici)1096-8628(19990115)82:2<132::aid-ajmg6>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Different mutations in the same codon of the proteolipid protein gene,PLP, may help in correlating genotype with phenotype in Pelizaeus-Merzbacher disease/X-linked spastic paraplegia (PMD/SPG2)

Abstract: Pelizaeus-Merzbacher disease/X-linked spastic paraplegia (PMD/SPG2) comprises a spectrum of diseases that range from severe to quite mild. The reasons for the variation in severity are not obvious, but suggested explanations include the extent of disruption of the transmembrane portion of the proteolipid protein caused by certain amino acid substitutions and interference with the trafficking of the PLP molecule in oligodendrocytes. Four codons in which substitution of more than one amino acid has occurred are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 22 publications
1
16
0
2
Order By: Relevance
“…In addition, the missense and nonsense mutations affecting Q233 resulted in the same mild form (3). The two different aa substitutions reported in the conservative aa 223 (L223P and L223I), 21 caused a severe form of PMD. However, severe forms of PMD were also reported in two mutations affecting the non-conservative aa 45 (L45P and L45R), 21 suggesting that any change in the extracytoplasmic A-B loop is deleterious for oligodendrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the missense and nonsense mutations affecting Q233 resulted in the same mild form (3). The two different aa substitutions reported in the conservative aa 223 (L223P and L223I), 21 caused a severe form of PMD. However, severe forms of PMD were also reported in two mutations affecting the non-conservative aa 45 (L45P and L45R), 21 suggesting that any change in the extracytoplasmic A-B loop is deleterious for oligodendrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to differences in hydrophobicity changes for the affected transmembrane helix C resulting from the substitution. 21 We classified the phenotype of the PLP-specific nonsense mutation in exon 3B (W144X) 22 as SPG, whereas the three patients were originally described as having a movement disorder (tremor, ataxia), apparently without spasticity, due to normal milestone achievement during the first year of life. In our series, SPG family 9 had a very similar PLP-specific abnormality: the five affected patients expressed a classical PMD3 or SPG phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Singlestrand conformation polymorphism (SSCP) analysis of the PLP1 gene was performed as described previously by researchers in the Department of Molecular Genetics, Indiana University, Indianapolis, Indiana (18). Control subjects were the healthy siblings of patients (with other non-PMD diseases).…”
Section: Methodsmentioning
confidence: 99%
“…Genetic studies of the PLP1 gene revealed a T494G transversion, which is responsible for replacement of valine 165 by glycine (18). MR images obtained at the age of 1 month were normal, but at 2 years 4 months of age, T2-weighted MR images showed diffuse, patchy, and symmetrically increased signal intensity within the white matter.…”
Section: Patientmentioning
confidence: 99%
“…An extensive collection of missense mutations (those mutations that result in amino acid substitution) in the PLP/DM20 gene exist. Certain amino acid codons have a particularly rich array of changes that offer an opportunity to investigate the consequences of a specific protein alteration on myelination and the clinical manifestations of PMD/SPG2 [139,140]. Three codons were mutated in two missense versions (V166E, V166G; L224I, L224P; Q234X, Q234P), and one codon was subjected to five different missense mutations: the aspartate at position 202 was changed to an asparagine, histidine, valine, glycine or glutamate residue in different PMD patients.…”
Section: Additional Genotype-phenotype Correlationsmentioning
confidence: 99%